2014
DOI: 10.5489/cuaj.510
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 8, 10, 12, 16, 20 cores prostate biopsies in determination of prostate cancer and importance of prostate volume

Abstract: Introduction: In this study, we evaluate the relationship between increasing core numbers and cancer detection rate. Methods: We included 1120 patients with prostate-specific antigen levels ≤20 ng/mL and/or suspicious digital rectal examination findings in this study. All patients had a first-time prostate biopsy and 8, 10, 12, 16, and 20 core biopsies were taken and examined in different groups during the study. Multiple logistic regression analysis was made to reach the factor affecting the cancer detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…This difference may be caused by differences in prostate volume (mean 44.82 vs. 31.9 ml) and serum PSA level (mean 9.73 vs. 8.58 ng/ml) between the two studies. Previous studies have identified patient subgroups with high positive rates in repeat biopsy; there are high false negative rates in patients with a large prostate volume and elevated serum PSA levels ( 20 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be caused by differences in prostate volume (mean 44.82 vs. 31.9 ml) and serum PSA level (mean 9.73 vs. 8.58 ng/ml) between the two studies. Previous studies have identified patient subgroups with high positive rates in repeat biopsy; there are high false negative rates in patients with a large prostate volume and elevated serum PSA levels ( 20 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite efforts made to identify new serum and biological markers and refinement of imaging modalities for the diagnosis of PCa, prostate biopsy performed with the guidance of TRUS is still the most important diagnostic method (8). In order to increase the cancer detection rate of prostate biopsy, various schemes have been applied in time such as sextant biopsy, extended biopsy and saturation biopsy (9). Treatment of patients, who are diagnosed not to have cancer in the first prostate biopsy despite persistently elevated levels of PSA, is a common problem for the urologist.…”
Section: Discussionmentioning
confidence: 99%
“…The indication for biopsy was the presence of prostatic nodules detected on DRE, which indicated that this type of examination may reveal tumors in men with a low PSA level [3]. In other studies also, no statistically significant differences were found between PSA levels by the number of cores [15,16,18]. …”
Section: Discussionmentioning
confidence: 99%